Sistem Retur Barang Pada Program Garansi Bebas Pengembalian di E-Commerce Shopee Perspektif Khiyar Syarat - Rohayati, Eti; Ja’far, A Kumedi; Faizal, Liky (Universitas Sang Bumi Ruwa Jurai, 2025)
The development of digital technology has driven the rapid growth of the e-commerce sector, one of which is through the Shopee platform which provides a Free Return Guarantee program. This program aims to increase consumer confidence by giving the right to return goods if they do not match the description, are damaged, or for reasons of